Musculoskeletal Tumor Imaging: An Orthopedic Oncologist Perspective - Sherman, Courtney E.; O'Connor, Mary I. (Seminars in Musculoskeletal Radiology, 2013)
Imaging of a musculoskeletal tumor or lesion is vital for the proper diagnosis and treatment of a patient. There are critical questions for the orthopedic oncologist that musculoskeletal imaging should answer. Is the lesion demonstrating benign or malignant characteristics? Where are the vital structures located in relationship to the lesion? Are there any other regional metastases? Where should an image-guided or open biopsy be performed to allow for limb salvage? What surgical resection will allow adequate margins with the goal of preserving as much function as possible? Decisions regarding biopsies and surgical planning are ideally made by a collaborative discussion between the treating orthopedic oncologist and the radiologist.
Keywords: sarcoma; biopsy; staging; tumor resection; orthopedic oncology